2022
DOI: 10.15343/0104-7809.202246199208
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with vocal problems in teachers from Montes Claros, Minas Gerais

Abstract: Os professores utilizam da voz como instrumento de trabalho e acabam se expondo a riscos de sobrecarga e esforço vocal, podendo prejudicar o desempenho profissional. Este estudo teve como objetivo verificar a prevalência e os fatores associados aos problemas vocais em professores durante a pandemia da Covid-19. Trata-se de um estudo transversal, analítico, formado por 82 professores do ensino fundamental de três escolas estaduais de Montes Claros, Minas Gerais, Brasil. Para avaliação dos problemas vocais utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Research has shown that the prevalence of vocal disorders during the pandemic was lower than during face-to-face classes due to using the voice with less frequency and intensity (Campos et al, 2022). Another critical point was observed in a study during the pandemic: teachers dissatisfied with their teaching work were among those who did not practice physical activity (Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the prevalence of vocal disorders during the pandemic was lower than during face-to-face classes due to using the voice with less frequency and intensity (Campos et al, 2022). Another critical point was observed in a study during the pandemic: teachers dissatisfied with their teaching work were among those who did not practice physical activity (Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%